Potential of endophytic fungi as biocontrol agents of Duponchelia fovealis (Zeller) (Lepidoptera:Crambidae) - Amatuzzi,R. F. (2018)
Abstract This study reports the first assessment of endophytic fungi isolated from strawberry leaves and selection of isolates for the control of Duponchelia fovealis, a new pest of strawberries. A total of 400 strawberry leaves of the cultivar ‘Albion’ were collected in four commercial farms. Leaves were disinfected, cut in fragments, and placed on Petri dishes containing potato dextrose agar media with tetracycline and incubated for 30 days. Following this time, 517 fungal colonies were isolated, and thirteen genera were identified: Cladosporium, Aspergillus, Nigrospora, Fusarium, Trichoderma, Chaetomium, Alternaria, Paecilomyces, Penicillium, Ulocladium, Bipolaris, Diaporthe, and Phoma. Eight isolates belonging to the genera Aspergillus, Diaporthe, Paecilomyces, and Cladosporium were selected for pathogenicity bioassays against third instar larvae of D. fovealis. Isolates of Paecilomyces induced the highest mortality rates.